2021
DOI: 10.1021/acs.jpcc.1c06702
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong Single-Crystal α-Bi4Br4 Nanobelts with a High Current-Carrying Capacity by Mechanical Exfoliation

Abstract: Mechanical exfoliation is of great potential in the preparation of two-dimensional (2D) materials such as graphene and transition metal dichalcogenides, offering new opportunities for exploring extraordinary electronic, optic, optoelectronic, and spintronic properties of low-dimensional materials. However, the extension of the exfoliation method from 2D van der Waals materials to one-dimensional (1D) materials has rarely been reported. Here, we show that the 1D α-Bi 4 Br 4 nanobelts can be prepared by direct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…[9,11] Previous studies reported that in some topological semimetals, the resistivity can decrease with the decreasing cross-sectional area of the conductors. [27][28][29]70] In our present study, the resistivity values that we obtained for nanoribbons of different sizes were not sufficient to claim the specific trend with the cross-section area within the standard error of the measurements. It was recently reported that annealing, i.e., due to heating or passing current, can improve the current conduction in thinner films of topological semimetals.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…[9,11] Previous studies reported that in some topological semimetals, the resistivity can decrease with the decreasing cross-sectional area of the conductors. [27][28][29]70] In our present study, the resistivity values that we obtained for nanoribbons of different sizes were not sufficient to claim the specific trend with the cross-section area within the standard error of the measurements. It was recently reported that annealing, i.e., due to heating or passing current, can improve the current conduction in thinner films of topological semimetals.…”
Section: Resultscontrasting
confidence: 76%
“…It is not possible to state at this point if the low level of noise in (TaSe 4 ) 2 I nanoribbons is due to the current fluctuation suppression in the topologically protected conductive channels of the Weyl semimetal. [68][69][70] The latter would require a dedicated theoretical study allowing to connect the electron scattering and capture rates with the fluctuations in the number of electrons and their mobility. The experimental data reported in this study indicate an unexpectedly low noise level and motivate future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the particular 1D atomic bonding makes 1D vdWMs prone to exist in the form of nanowires [97], nanotubes [101], nanoribbons [115], nanofibrous [116], nanobelts [117], and other ganging morphologies, which is adverse to the construction of device array. Compared to 1D vdWMs, the large-scale preparation of 2D vdWMs is much simpler, laying a solid foundation for the on-chip integration of corresponding functional devices.…”
Section: D Vdwm Polarized Photodetectorsmentioning
confidence: 99%
“…In this consideration, the polarization-dependent photosensitivity of photodetectors built of novel low-symmetry vdWMs (e.g. MoI 3 [79], Nb 2 Se 9 [287], α-Bi 4 Br 4 [117], Ta 2 Ni 3 Se 8 [288], GePdS 3 [58], CrSbSe 3 [289], BiSeI [290], Ta 2 Se 3 [291], AsSbO 3 [292], AsSbS 3 [293]…”
Section: Optoelectronic Anisotropy Of Novel Low-dimensional Vdwms And...mentioning
confidence: 99%